2013
DOI: 10.2478/10004-1254-64-2013-2307
|View full text |Cite
|
Sign up to set email alerts
|

Is Burnout in Family Physicians in Croatia Related to Interpersonal Quality of Care?

Abstract: The impact of physician burnout on the quality of patient care is unclear. This cross-sectional study aimed to investigate the prevalence of burnout in family physicians in Croatia and its association with physician and practice characteristics, and patient enablement as a consultation outcome measure. Hundred and twenty-fi ve out of 350 family physicians responded to our invitation to participate in the study. They were asked to collect data from 50 consecutive consultations with their adult patients who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The correlation between workload and emotional exhaustion ( Table 2 ), supported by the findings highlighting difficult working conditions in Slovenian primary health care, with 90% of physicians dealing with at least 40 patients and 20% with at least 60 patients per day ( Table 2 ), is concordant with a previous Slovenian study of family medicine trainees and Croatian FMDs ( 21 , 37 ). An additional burden was demonstrated in those working in rural family medicine clinics ( Table 3 ), which is concordant with the study in which those working in rural settings scored higher on the MBI ( 28 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The correlation between workload and emotional exhaustion ( Table 2 ), supported by the findings highlighting difficult working conditions in Slovenian primary health care, with 90% of physicians dealing with at least 40 patients and 20% with at least 60 patients per day ( Table 2 ), is concordant with a previous Slovenian study of family medicine trainees and Croatian FMDs ( 21 , 37 ). An additional burden was demonstrated in those working in rural family medicine clinics ( Table 3 ), which is concordant with the study in which those working in rural settings scored higher on the MBI ( 28 ).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, organisational issues are shown to be a high risk factor for burnout ( Table 2 ), high workload being an issue in Slovenia as well as in other developed countries ( 3 , 15 , 37 ). The situation in the country, with an aging population, the lack of physicians working in primary care, a decrease in interest in family medicine residencies, and shortage of time for the patient ( 48 ), suggests an urgent need for psychological help and support for FMDs, taking into consideration empathic attitude, which is associated with the feeling of personal accomplishment.…”
Section: Discussionmentioning
confidence: 67%
“…However to our knowledge, the relationship between family physician job stress factors and patient coping with health trouble has never been investigated. One study has explored potential links between patient enablement and FP burnout and reported negative results [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that GPs with lower sense of personal accomplishment used less affective communication and were less patient-centred35 and that patients listed with more depersonalised and emotionally exhausted GPs were less satisfied with the consultations with their GP 36. However, other studies found no indications that burnout or job dissatisfaction impaired the quality of interpersonal care 37–39. Some of these differences may be attributable to different burnout definitions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high conscientiousness could be a risk factor for burnout. Thus, emotionally exhausted GPs may exhibit high levels of thoroughness and attentiveness to patients’ needs in clinical encounters, and hence their patients may experience excellent care 3 38 42. In later stages of burnout, carelessness and disengagement may become more dominant.…”
Section: Discussionmentioning
confidence: 99%